When the Law is Blunt to the Perpetrator: A Critique of the Criminal Provisions for Physical Violence against Wives and the Weak Protection of Victims - Ardelia Rahmadani; Sutiawati Sutiawati; Muhammad Adnan Lira (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study aims to analyze the criminal law provisions governing the crime of physical violence against wives within the household and to assess the extent to which legal protection for victims has been implemented from a victim-oriented perspective. The research method used is normative juridical legal research with statutory and conceptual approaches. The legal materials used consist of primary, secondary, and tertiary legal materials, which are analyzed using a qualitative descriptive method. The results of the study indicate that the criminal law provisions in Indonesia regulating physical violence against wives in the household are stipulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which provides special protection for victims and establishes criminal sanctions for perpetrators of violence. Legal protection for victims of physical violence against wives in the household is carried out through preventive and repressive measures. Preventive protection is implemented by strengthening social networks, understanding local cultural wisdom and religious values, and reinforcing the economic foundations of the family. Meanwhile, repressive protection is provided through temporary protection and protection based on court orders. This study recommends that the government and law enforcement officials optimize the implementation of criminal provisions stipulated in legislation, particularly by strengthening victim protection mechanisms, legal assistance, and psychological and social recovery. In addition, increased coordination among relevant institutions, legal awareness campaigns for the community, and more effective supervision in the law enforcement process are needed to ensure that victims receive maximum protection and that perpetrators receive sanctions that create a deterrent effect.